Correction: Wei et al. Sensitivity of Vegetation to Climate in Mid-to-High Latitudes of Asia and Future Vegetation Projections. Remote Sens. 2023, 15, 2648 - Jiangfeng Wei; Xiaocong Liu; Botao Zhou (Remote Sensing)
There was a typographical error in the original publication [...]